2013
DOI: 10.1037/a0033790
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of addiction, attempts to quit, and successful quitting in nondaily and daily smokers.

Abstract: We aimed to qualitatively examine differences in perceptions of addiction, attempts to quit, and successful quitting among nondaily versus daily college student smokers. We conducted 16 focus groups with a total of 73 college student smokers from the southeastern U.S. Focus groups were homogenous in terms of gender, smoking status (nondaily, daily), and type of school (2-year college, 4-year university). Questions centered on perceptions of addiction, their own addiction, what constitutes a quit attempt, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 43 publications
3
30
0
2
Order By: Relevance
“…For example, questions include “age when first started smoking regularly,” “age when smoked a whole cigarette,” and “age when smoked part or all of a cigarette”. The age when a person starts to smoke cigarettes regularly may be associated with addiction and may be disregarded by persons who do not consider themselves to be regular smokers 67 . As noted previously, African Americans tend to initiate tobacco use later in life 26 , 68 , 69 compared with whites and are more likely to be nondaily smokers 70 .…”
Section: Methodsmentioning
confidence: 98%
“…For example, questions include “age when first started smoking regularly,” “age when smoked a whole cigarette,” and “age when smoked part or all of a cigarette”. The age when a person starts to smoke cigarettes regularly may be associated with addiction and may be disregarded by persons who do not consider themselves to be regular smokers 67 . As noted previously, African Americans tend to initiate tobacco use later in life 26 , 68 , 69 compared with whites and are more likely to be nondaily smokers 70 .…”
Section: Methodsmentioning
confidence: 98%
“…Frequent reference to physical withdrawal symptoms occurred across studies including headaches 58 , insomnia 54 , nausea 59 , concentration difficulties 54,59 , shakiness 63,68 , cold sweats and dry mouth 63 . Smoking cigarettes relieved these symptoms, but was also associated with pleasure in the form of "a tingly feeling" 69 , a "buzz" 70 , a pleasurable smell and taste 74 , or an enjoyable feeling "going down my throat" 65 .…”
Section: What Does Addiction Look Like To Smokers?mentioning
confidence: 99%
“…A higher or lower level of tobacco addiction can have an impact on the ability of a person to remain smoke-free. A research study carried out in the Southeast region of the US with 73 university students, some of whom smoked daily and others who used cigarettes occasionally, showed that the latter presented lower addiction and, therefore, a higher ability to quit smoking, while daily smokers report-ed symptoms of tobacco addiction and an inability to control this dependency (15) . In Brazil, a study conducted with people incapable of quitting the smoking habit even with the help of cognitive-behavioral therapy groups indicated the difficulty smokers had in dealing with nicotine withdrawal symptoms, psychological addiction, and behaviors associated with the smoking habit (16) .…”
Section: Discussionmentioning
confidence: 99%